“FISH BOX PERLTIER COOLER” FISH COLLING BOX EQUIPPED WITH PELTIER ELECTRIC COOLER (PEC) - Achmat Soleh Soleh; Rio Antoni; Alfian Dwi Cahyo; Muhammad Rifandiansyah; Joseph Mochammad Saputra (Journal of the Community Development in Asia (JCDA), 2018)
The purpose of this study is to provide solutions to problems that exist in SMEs D.Sadewa Kenjeran Coast region in the process of cooling and storage of marine products is traditionally the process is still using ice as the cooler in the box (box) fish storage. The method used by using PEC in the box of fishes storage to produce stable temperature. The PEC box control system is equipped with Arduino and programmed with CX programmer. It is designed to accommodate 15kg of fish /process. The expected result is to improve the stability of the cooling process (below 100C), So the productivity of SMEs can be increased twice .